The population ecology of fathead minnows (Pimephales promelas) in estrogen contaminated environments - Schwindt, Adam Richard, author; Winkelman, Dana L., advisor; Clements, William, committee member; Myrick, Chris, committee member; Ramsdell, Howard, committee member (Colorado State University. Libraries, 2013)
Urban freshwater streams and rivers in arid climates are ecosystems dominated by wastewater effluent. Effluent contains a suite of bioactive chemicals including steroid and non-steroid estrogens that have been shown to disrupt vertebrate endocrine systems in laboratory studies. One of these steroid estrogens is 17alpha-ethinylestradiol (EE2), a synthetic steroid estrogen used in human oral contraceptives. EE2 enters waterways after incomplete removal during wastewater treatment and can disrupt reproduction in fishes. However, little understanding exists of the ecological consequences of reproductive disruption. My studies were initiated to evaluate how xenoestrogens might influence the population ecology of aquatic vertebrates. Specifically, I assessed the population ecology of fathead minnows (Pimephales promelas), a short-lived fish, that were exposed to early-life, life-time, and adult exposures of EE2. While assessment at the population-level was the goal, an understanding of environmental chemistry and ecotoxicology was needed to fully characterize the effects and consequences of EE2 and this is reflected in my dissertation that is organized into four chapters. Chapter 1, "Influence of community productivity on an estrogen added to aquatic mesocosms" identified chlorophyll a and nitrate as explanatory factors associated with the partitioning of EE2 to organic matter. In addition, it details the development of a high performance liquid chromatography tandem mass spectrometry method capable of quantifying EE2 at sub nanogram per liter concentrations. The method afforded the ability to accurately measure EE2 concentrations during the experiments. Chapter 2, "Linking multiple biomarkers and varying exposure history in estrogen contaminated environments: is a comprehensive profile of fish health possible?" concludes that EE2 induces many physiological changes in fish at multiple levels of biological organization. Our results suggest that, depending on the timing of exposure (early-life, life-time or exposure as an adult), linking effects between biomarkers may be possible. Here we also demonstrate that the EE2 concentrations used in our experiments are environmentally relevant because fish caged below a wastewater treatment plant displayed a similar physiological response as the fish in the experiments. Chapter 3 "Fish population failure caused by an environmental estrogen is long-lasting and regulated by direct and parental effects on survival and fecundity" presents the effects of EE2 on population dynamics with empirically derived results from a one year long series of experiments. This chapter is the first to demonstrate that an early-life EE2 exposure to the parents causes reduced offspring survival despite the offspring never being directly exposed to EE2. Additionally, we found that an early-life exposure to EE2 caused permanent reproductive disruption and life-time exposures caused reproductive failure. Surprisingly, the summer long exposure to adult fish induced significant declines in male survival culminating with 100% mortality at the highest concentrations. In chapter 4, "A stochastic stage-structured modeling approach to evaluate the effects of estrogenic exposure on population growth rate in a short-lived fish" we demonstrate that EE2 can drastically reduce population growth rate (PGR) mediated by reduced reproductive output and juvenile survival. Declines in PGR were evident despite the lack of statistical significance on the effects of EE2 on egg, embryo, and juvenile fish production seen in the experimental data. Overall my research demonstrates that by taking a holistic approach we can better understand the potential population-level and multigenerational effects of EE2, and the consequences for population growth.